A Unified Deflection Theory Model for Multi-Tower Self-Anchored Suspension Bridges with Different Tower–Girder and Cable–Girder Connections - Shiyu Guan; Dinghui Liao; Yi Zhang; Jun Shi; Shuang Liu; Hongyou Cao (Buildings)
This study presents a unified analytical model for multi-tower self-anchored suspension bridges integrating tower–girder connections (TGCs) and cable–girder connections (CGCs) within the framework of deflection theory. The connections are modeled as horizontal springs, and governing equations are derived based on force equilibrium and compatibility conditions. A comparison with a nonlinear finite element analysis under various live load scenarios confirms the accuracy of the proposed model. A parametric analysis reveals that increasing the CGC stiffness reduces girder deflection, decreasing the maximum vertical deflection by nearly 42.3% when the stiffness is increased from 0 to infinity and moving the maximum displacement from the mid-span section to the mid-tower section. Additionally, CGCs modify the load distribution between the main cable and the girder, limiting the longitudinal displacement of the tower in which the mid-tower displacement is reduced by 45.50%. Tower–girder connections improve the anchoring of the side cable to the tower. When connection stiffness is low, side- and middle-tower stiffness significantly reduce girder deflection, though this effect decreases with increasing stiffness. Enhancing mid-tower stiffness similarly reduces its longitudinal displacement regardless of the tower–girder connection. In longitudinal floating systems, mid-tower displacement rises with increasing side-tower stiffness. Establishing a unified analysis model reveals the key parameters in the structural analysis of suspension bridges, enabling an easier and faster analysis of multi-tower self-anchored suspension bridges.